Mendorong Partisipasi Bina Keluarga Lansia (BKL) dalam Mewujudkan Tujuh Dimensi Lansia Tangguh di Desa Sumbersari, Moyudan, Sleman - Eka Zuni Lusi Astuti; Tri Winarni (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2018)
Bina Keluarga Lansia (BKL) is one of the government programs to empower the elderly and their families. Through this program the elderly are expected to apply 7 dimensi lansia tangguh so that the elderly are physically, emotionally, spiritually, intellectually, socially, professionally vocational and environmentally empowered. The existence of BKL is needed in every hamlet. However, in Sumbersari Village, Moyudan, Sleman, out of five BKLs already established, only one BKL, BKL Mugi Waras, with a paripurna status that applied 7 dimensi lansia tangguh in its activities. Therefore, the community service program of the development of the targeted village aims to replicate BKL Mugi Waras to other BKL which have basic status. The activity used for community service were socialization and education in various training for strengthening BKL institutionally. The program has shown positive impacts on understanding managing BKL and applying 7 dimensi lansia tangguh on its activities.